1984
DOI: 10.1021/jo00197a054
|View full text |Cite
|
Sign up to set email alerts
|

Acid-catalyzed cyclization of terpenoids in a micellar system. Selectivity and rate enhancement in the cyclization of citronellal

Abstract: 45 °C for 0.5 h. Sodium hydride (0.25 mmol) (10 mg of 60% NaH dispersed in mineral oil washed with petroleum ether) was added to the solution. After cessation of gas evolution 0.5 mL of 5% DC1 was added. TLC on silica gel (9% MeOH in CH2C12, UV visualization) showed only the ring-contracted product 3 had formed; this was confirmed by proton NMR on the reaction mixture.Acknowledgment. We thank E. Reich for elemental analyses, M. Mentzer for mass spectral data, and D. Staiger and G. Zuber for some of the NMR dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 3 publications
2
26
0
Order By: Relevance
“…[19][20][21] We confirmed this experimentally: in addition to minor products 3a-d, a mixture of four stereoisomeric p-menthane-3,8-diols (4) is observed as the major class of products. Once formed, 4 may undergo condensation with 2 to generate pmenthane-3,8-diol citronellal acetal stereoisomers (5).…”
Section: Introductionsupporting
confidence: 60%
“…[19][20][21] We confirmed this experimentally: in addition to minor products 3a-d, a mixture of four stereoisomeric p-menthane-3,8-diols (4) is observed as the major class of products. Once formed, 4 may undergo condensation with 2 to generate pmenthane-3,8-diol citronellal acetal stereoisomers (5).…”
Section: Introductionsupporting
confidence: 60%
“…In the three studies, the syntheses led to a mixture of PMD, isopulegol, citronellal and an acetal (p-menthane diol citronellal acetal); and led to a mixture of stereosiomers of PMD. Following the work of Lett and Kraus (1992), the experimental conditions have been extensively optimized to favor the cis isomer [cristallisation at low temperatures (Shiroyama et al, 2001;Komatsuki et al, 2013), addition of surfactants (Clark et al, 1984;Dell, 2010Dell, , 2013 or phase transfert agents (Xuedong, 2013)].…”
Section: Syntheses Of Pmdmentioning
confidence: 99%
“…Citric acid was used as an alternative natural catalyst (Schöftner, 2015), but led to modest cis/trans ratios (48/52-55/45). Micelles were also added to the citric acid catalyzed reaction and decreased its acidity (Clark et al, 1984). Although these methods using citric acid seem to be more environment-friendly, they require systematic work-up processes, neutralization and extraction, which generate unsatisfactory Sheldon factors (mass ratio of waste to desired product).…”
Section: Syntheses Of Pmdmentioning
confidence: 99%
“…11 The formation of l-IPG from d-CTN using Lewis acids (ZnCl 2, ZnBr2 and ZnI2) was reported to be highly stereoselective; the yield and selectivity were 70% and 90%, respectively, under optimum reaction conditions. 12 For the isomerization of CTN in chloroform, dichloromethane, and n-hexane as solvents using acid clinoptilolite, mordenite and faujasite zeolites, both the activity and the selectivity were related to the total amount of Brönsted acid sites and the textural properties of the catalysts. It was found that only a fraction of acid sites located at the external surface of catalyst was responsible for the formation of isopulegol ether due to the diffusional resistance.…”
Section: Introductionmentioning
confidence: 98%
“…The conversion of citronellal (CTN) to isopulegol (IPG) over acid catalysts has drawn much attention in both academic and industrial research because IPG is an important intermediate for the synthesis of menthol, a raw material for the manufacture of pharmaceuticals, cosmetics, flavors, and toothpastes. 1 This reaction was traditionally performed in the liquid phase using various homogeneous or heterogeneous catalysts such as aqueous sulfuric acid, 2 acetic anhydride, 3 tris(triphenylphosphine) rhodium chloride, 4 molybdenum and tungsten carbonyl complexes, 5 scandium trifluoromethanesulfonate, 6 heterogeneous Lewis acid, 7 superacids, 8 single or mixed metallic oxides, [9][10][11] metal salts, 7,9 micellar catalysts, 12 zeolites, 13 sulfated zirconia-carbon molecular sieve composite catalysts 14 as well as hydrous zirconia and clays. 15 With a superacid such as FSO 3 H/SO 2 , IPG and neoisopulegol were produced via cyclization that followed the same reaction path as the normal acids.…”
Section: Introductionmentioning
confidence: 99%